Oxide Single-Crystal Surfaces: A Playground for Self-assembled Oxide Nanostructures - Bachelet, Romain (Frontiers in Physics, 2016)
The different (structural and chemical) properties of oxide single-crystal surfaces that can be exploited for the growth of self-assembled oxide nanostructures are briefly reviewed. A large variety of nanostructures can be obtained, controlled by surface and interface structure and chemistry, which play a predominant role in their formation mechanisms at this nanometer scale. It is reminded that surface atomic order, surface steps, chemical terminations or heteroepitaxial strain can be used to generate various nanostructures such as nanodots, nanowires, nanostripes, with controlled size, morphology and spatial ordering.